Low-dose extracorporeal shock wave attenuates sepsis-related acute lung injury by targeting mitochondrial dysfunction and pyroptosis crosstalk in type II alveolar epithelial cells - Guo, Jianning; Qu, Xiaoxuan; Ge, Ruidong; Liu, Die; Liu, Jing; Hui, Qin; Ye, Fang; Chen, Yuanmei; Wang, Chao; Lv, Di; Tang, Lijuan; Xia, Meihong; et al. (Frontiers in Immunology, 2025)
IntroductionThe pathological mechanism of sepsis-related acute lung injury (ALI) is closely linked to mitochondrial dysfunction and pyroptosis. Although low-dose extracorporeal shock wave (SW) therapy has been widely utilized in tissue and organ injury repair, its role in sepsis-related ALI remains unclear. This study aimed to elucidate the regulatory mechanisms of SW on mitochondrial pyroptosis crosstalk in septic ALI.MethodsThe sepsis-related ALI mouse model was induced by tail vein injection of LPS. In vitro, LPS and ATP induced a pyroptosis model in type II alveolar epithelial (AT2) cells. The levels of inflammatory factors and oxidative stress were detected. The ultrastructure of lung mitochondria was observed by transmission electron microscope. Moreover, the mitochondrial membrane potential, ATP content, and the level of mtDNA were determined in cells and tissues. Western blot was used to detect mitochondrial oxidative stress and dysfunction, as well as the expression of pyroptosis-related proteins mediated by NLRP3 inflammasome.ResultsSW significantly reduced the secretion levels of inflammatory factors TNF-α, IL-1β, IL-6, and IL-8 in serum, alveolar lavage fluid (BALF), and cell supernatant, inhibited oxidative stress markers (ROS, MDA, MPO), and upregulated antioxidant index (SOD, GSH). Pathological evidence indicates that SW can alleviate the pathological changes of lung injury and restore the mitochondrial ultrastructure of AT2 cells. The mechanism study shows that SW can enhance mitochondrial membrane potential and ATP production, inhibit mtDNA migration and p65 nuclear translocation, and down-regulate the expression of mitochondrial coding genes (MT-ND2, MT-ND4) and iNOS. At the same time, SW inhibited the NLRP3/ASC/Caspase-1 signaling axis, thereby disrupting pyroptosis cascades.ConclusionThis study reveals that SW attenuates septic ALI by targeting mitochondrial-pyroptosis crosstalk, offering a novel non-invasive therapeutic strategy for clinical applications.